A New Class of Analytic Functions Associated with Sălăgean Operator. (3rd February 2019) - Arif, Muhammad; Ahmad, Khurshid; Liu, Jin-Lin; Sokół, Janusz
Abstract : The main object of the present paper is to investigate a number of useful properties such as inclusion relation, distortion bounds, coefficient estimates, and subordination results for a new subclass of analytic functions which are defined here by means of a linear operator. Several known consequences of the results are also pointed out.